Engaging with the Margins: Patterns of Transformation in the Baptist Ministry to the Bulgarian Roma - Aleksandravicene, Victoria (Journal of European Baptist Studies, 2024)
The Baptist evangelical mission among the Bulgarian Roma traces its roots to the beginning of the twentieth century. Waves of persecution, discrimination, and a hate-speech narrative have continuously placed the Roma community at the fringes of society. Despite ineffectual state efforts and strategies, many churches manage to make a difference in the lives of the Roma in their surrounding communities. The church adopts a holistic approach — meeting spiritual needs, together with physical and social needs. This article provides an overview of the development of Baptist mission to the Roma people, its transformative outcomes, and its impact on both church life and the surrounding community.